The Role of Physiotherapy In Physical Fitness To Measure Balance and Coordination - Putra, Ida Bagus Acarya; Permadi, Agung Wahyu; Yasa, I Made Astika; Parwata, I Made Yoga (Healthy Tadulako Journal (Jurnal Kesehatan Tadulako), 2025)
Background: Physical fitness reflects the body’s ability to perform activities efficiently, supported by optimal balance and coordination. Objective: This study aimed to determine the effect of physiotherapy balance board exercises on improving balance and coordination among students at Dhyana Pura University. Methods: A pre-experimental one-group pre-test post-test design was applied using purposive sampling with 20 participants meeting the inclusion and exclusion criteria. Balance and coordination were assessed using the Standing Stork Test and Hand Wall Toss Test, respectively, before and after 12 training sessions conducted over four weeks. Results: The findings showed a notable improvement in balance, with increases of 22.4% for the right leg and 21.6% for the left leg, alongside a 24.8% enhancement in coordination after the training intervention. Statistical analysis using the paired-sample t-test indicated a significant difference in both balance and coordination (p = 0.000, p < 0.005), confirming a normal distribution and meaningful post-training improvement. These results demonstrate that consistent physiotherapy-based balance board exercises effectively enhance neuromuscular control, stability, and coordination performance. Conclusion: Balance board exercises significantly improve both balance and coordination, highlighting their effectiveness as a physiotherapeutic intervention to enhance physical fitness among university students.